Digital Transformation Management in Cyber Islamic Universities: A Value Ecosystem Approach - Ripai, Ahmad; Santoso, Sigit; Kardipah, Saepah (JURNAL AL-TANZIM, 2026)
This study explores the strategic challenges faced by Islamic higher education institutions in adapting to digital disruption in the context of the Industrial Revolution 4.0 and Society 5.0. The research aims to analyze how digital transformation management is implemented in cyber-based Islamic universities, with a focus on expanding educational access and strengthening global outreach. A qualitative approach with a case study design was used, involving in-depth interviews, observations, and document analysis with institutional leaders, academic staff, and students. The findings reveal that digital transformation is achieved through an integrated management approach that includes strategic planning, adaptive governance, and organizational change. Key implementations include digital infrastructure development, management of online learning systems, and integration of value-based digital literacy. The study emphasizes the importance of aligning technological innovations with leadership commitment and institutional strategies to uphold Islamic values. This research contributes to the field by providing a conceptual and practical framework for digital transformation management, highlighting the need for governance, leadership, and value-oriented strategies to ensure an inclusive and sustainable transformation of higher education.